Low-temperature high-elasticity ultraviolet-resistant rubber base plate as well as preparation method and application thereof

By blending natural rubber, butyl rubber and ethylene propylene ternary rubber and adding specific additives, the problem of rubber pads falling elastically and aging in extremely low temperatures and ultraviolet environments is solved, and the service life and performance improvement in railway construction in high latitudes and plateau areas is achieved.

CN119505325AInactive Publication Date: 2025-02-25HEBEI TIEKE YICHEN NEW MATERIAL TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510065600.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-16
Publication Date
2025-02-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing rubber pads have decreased elasticity in extremely low temperature environments and are not resistant to ultraviolet aging, resulting in short service life and premature damage in railway construction in high latitude and plateau areas.

Method used

Natural rubber, butyl rubber and ethylene propylene ternary rubber are blended as the main components, and compatibility is improved through the segmented kneading process and the composite vulcanization system, and additives such as 2-(2'-hydroxy-3',5'-dibutylphenyl)benzotriazole, 4,4'-bis(α,α-dimethylbenzyl)dianyl and silane coupling agent are added to improve anti-aging performance.

Benefits of technology

Maintain good elastic properties at room temperature, the elastic change rate is small at -50℃, and it maintains high elasticity. It also has excellent UV aging resistance, extending the service life of the rubber pad.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention belongs to the technical field of rubber base plates, and provides a low-temperature high-elasticity ultraviolet-resistant rubber base plate and a preparation method and application thereof.The low-temperature high-elasticity ultraviolet-resistant rubber base plate is prepared from a component I, a component II and a component III according to the mass ratio of (2-3): (1-2): 1; each of the component I and the component III is prepared from the following components in parts by mass: 100 parts of raw rubber, 3 to 5 parts of zinc oxide, 1.5 parts of stearic acid, 40 to 80 parts of filler, 1 to 4 parts of silane coupling agent Si75, 5 to 10 parts of 2-(2 '-hydroxy-3', 5 '-ditert-amylphenyl) benzotriazole, 3.5 parts of 4, 4'-bis (alpha, alpha-dimethylbenzyl) diphenylamine, 6 parts of anti-aging agent, 2.3 parts of accelerant, 2 to 3 parts of masterbatch S-80 and 0.3 to 0.7 part of DCP (dicumyl peroxide). Wherein the raw rubber in the component I, the component II and the component III is natural rubber, butadiene rubber and ethylene propylene diene monomer respectively. The prepared rubber base plate has good elasticity at normal temperature, still keeps high elasticity at the extremely low temperature of-50 DEG C, and meanwhile has excellent ultraviolet aging resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of rubber pads, and relates to a low-temperature, high-elasticity, UV-resistant rubber pad, and a preparation method and application thereof. Background Art

[0002] As the speed requirements of trains continue to increase, the importance of rubber pads in track vibration reduction systems has become increasingly prominent. As an indispensable component of the track structure, rubber pads elastically connect rails and sleepers, effectively absorbing and buffering the vibration and impact force generated by the passing of trains, thereby protecting the roadbed and track structure from damage. At the same time, it significantly improves the smoothness of train operation and the riding comfort of passengers, and effectively reduces vibration and noise.

[0003] Ordinary rubber pads can play a good vibration reduction and noise reduction effect at room temperature, but in cold areas such as high latitudes and plateaus, there will be a significant decrease in elasticity, and extreme low temperatures can easily cause the pads to crack and break. In addition, in addition to the low temperature environment, the plateau environment also has a high ultraviolet intensity (the ultraviolet intensity increases by about 1.3% for every 100 meters increase in altitude), which will accelerate the aging of the rubber pads. At the same time, the obvious elasticity loss seriously affects the stability of the train operation. The premature damage of the rubber pads seriously affects the operation of the train, and the replacement process of the pads will also consume a lot of manpower and material resources.

[0004] Therefore, in view of the current situation, it is very necessary to study a rubber pad that is highly elastic at room temperature, maintains high elasticity under extreme environments, and has certain resistance to ultraviolet aging to meet the needs of railway construction in high-latitude and plateau areas. Summary of the invention

[0005] The present invention proposes a low-temperature, highly elastic, UV-resistant rubber pad, and a preparation method and application thereof. The rubber pad prepared by the present invention has good elastic properties at room temperature. At an extremely low temperature of -50°C, the elasticity change rate is smaller than that of other rubber pads, and it still maintains a relatively high elasticity, and at the same time has excellent UV aging resistance.

[0006] The technical solution of the present invention is achieved in this way: A low-temperature, high-elasticity, UV-resistant rubber pad, the raw materials of which include component I, component II and component III in a mass ratio of 2-3:1-2:1; in component I to component III, by mass, each includes 100 parts of raw rubber, 3-5 parts of zinc oxide, 1.5 parts of stearic acid, 40-80 parts of filler, 1-4 parts of silane coupling agent Si75, 5-10 parts of 2-(2′-hydroxy-3′,5′-di-tert-pentylphenyl)benzotriazole, 3.5 parts of 4,4′-bis(α,α-dimethylbenzyl)diphenylamine, 6 parts of antioxidant, 2.3 parts of accelerator, 2-3 parts of masterbatch S-80, 0.3-0.7 parts of DCP, wherein the raw rubber in component I, component II and component III is natural rubber, butadiene rubber and ethylene propylene diene monomer rubber, respectively.

[0007] Specifically: Component I comprises, by mass, 100 parts of natural rubber, 3-5 parts of zinc oxide, 1.5 parts of stearic acid, 10-20 parts of carbon black N550, 20-30 parts of kaolin, 5-20 parts of aluminum silicate, 5-10 parts of talc, 1-4 parts of silane coupling agent Si75, 5-10 parts of 2-(2′-hydroxy-3′,5′-di-tert-pentylphenyl)benzotriazole, 3.5 parts of 4,4′-bis(α,α-dimethylbenzyl)diphenylamine, 3 parts of antioxidant RD, 3 parts of antioxidant H71, 0.8 parts of accelerator DTDM, 1.5 parts of accelerator CZ, 2-3 parts of masterbatch S-80, and 0.3-0.7 parts of DCP; Component II, by mass, includes 100 parts of butadiene rubber, 3-5 parts of zinc oxide, 1.5 parts of stearic acid, 10-20 parts of carbon black N550, 20-30 parts of kaolin, 5-20 parts of aluminum silicate, 5-10 parts of talc, 1-4 parts of silane coupling agent Si75, 5-10 parts of 2-(2′-hydroxy-3′,5′-di-tert-pentylphenyl)benzotriazole, 3.5 parts of 4,4′-bis(α,α-dimethylbenzyl)diphenylamine, 3 parts of antioxidant RD, 3 parts of antioxidant H71, 0.8 parts of accelerator DTDM, 1.5 parts of accelerator CZ, 2-3 parts of masterbatch S-80, and 0.3-0.7 parts of DCP; Component III, by mass, includes 100 parts of EPDM rubber, 3-5 parts of zinc oxide, 1.5 parts of stearic acid, 10-20 parts of carbon black N550, 20-30 parts of kaolin, 5-20 parts of aluminum silicate, 5-10 parts of talc, 1-4 parts of silane coupling agent Si75, 5-10 parts of 2-(2′-hydroxy-3′,5′-di-tert-pentylphenyl)benzotriazole, 3.5 parts of 4,4′-bis(α,α-dimethylbenzyl)diphenylamine, 3 parts of antioxidant RD, 3 parts of antioxidant H71, 0.8 parts of accelerator DTDM, 1.5 parts of accelerator CZ, 2-3 parts of masterbatch S-80, and 0.3-0.7 parts of DCP; Preferably, the surface of the rubber pad is coated with a coating film, and the raw materials of the coating film include, by weight, 100 parts of EPDM rubber, 4-6 parts of MgO, 1-3 parts of stearic acid, 55-65 parts of phenolic resin, 25-35 parts of carbon black N330, 8-12 parts of 2-(2′-hydroxy-3′,5′-di-tert-pentylphenyl)benzotriazole, 4-6 parts of 4,4′-bis(α,α-dimethylbenzyl)diphenylamine, 1.5-2.5 parts of accelerator PZ, 1-2 parts of sulfur, and 0.4-0.6 parts of DCP.

[0008] Preferably, the method for preparing the coating film comprises the following steps: Cut the EPDM rubber into small pieces of 1-3 mm; add the cut EPDM and other raw materials into cyclohexane and continue stirring for 8 hours to obtain a solution, wherein the amount of cyclohexane is: 1 g of the raw material is dissolved in 20 ml of cyclohexane; The obtained solution is poured into a rubber mill and ground for 25-35 minutes to obtain a coating solution, wherein the parameters of the rubber mill are as follows: voltage 380V, power 1.1kw, rotation speed 1500-2500rpm, emulsification fineness 25-35μm.

[0009] Preferably, the coating method of the coating solution comprises the following steps: The coating solution is applied on the surface of the obtained rubber pad, with a coating thickness of 0.2-0.4 mm and a coating amount of 1.0-1.2 g / cm 2 , and air-dry at room temperature for 1.5-3 hours; the four sides or all surfaces can be coated; Use thermal equipment to heat the narrow edge of the pad at 160-180°C for 1.5-3 minutes to solidify the periphery of the pad to obtain the product.

[0010] Preferably, the brand of the natural rubber is RSS3; the brand of the butadiene rubber is BR9000; and the brand of the ethylene propylene diene monomer rubber is EPDM4045.

[0011] Preferably, the filler is selected from one or more of carbon black N550, white carbon black, kaolin, aluminum silicate and talc.

[0012] Preferably, the antioxidant is antioxidant RD and / or antioxidant H71; the accelerator is accelerator DTDM and / or accelerator CZ.

[0013] Preferably, the filler consists of 10-20 parts of carbon black N550, 20-30 parts of kaolin, 5-20 parts of aluminum silicate, and 5-10 parts of talc; The antioxidant is composed of 3 parts of antioxidant RD and 3 parts of antioxidant H71; The accelerator is composed of 0.8 parts of accelerator DTDM and 1.5 parts of accelerator CZ.

[0014] The present invention also provides a method for preparing the above-mentioned low-temperature, high-elasticity, UV-resistant rubber pad, comprising the following steps: A. Mix components I to III separately: The mixing method of component I comprises the following steps: adding raw rubber into an internal mixer, adding zinc oxide, stearic acid, filler, silane coupling agent, 2-(2′-hydroxy-3′,5′-di-tert-pentylphenyl)benzotriazole, 4,4′-bis(α,α-dimethylbenzyl)diphenylamine, antioxidant, accelerator, masterbatch S-80 and DCP to obtain a mixed rubber, wherein the mixing temperature is 85-100° C., the rotation speed is 20-40 rpm, and the mixing time is 8-12 minutes; the mixing method of component II and component III is the same as that of component I; B. Put the mixed rubber obtained from component I to component III into an internal mixer for mixing at a mixing temperature of 85-100°C, a rotation speed of 20-40 rpm, and mixing for 3-8 minutes; C. Add the mixed rubber obtained in step B into an open rubber mixer, use the default roller speed, adjust the roller distance to the minimum, pass cooling water, control the roller temperature to be no higher than 75° C., mix the rubber in the mixer, sheet the rubber 3-5 times, make triangle bags 3-5 times to obtain a film, park it for 12 hours, and then extrude it into a film using a cold feed extruder; D. Put the formed film obtained in step C into a flat vulcanizer for vulcanization treatment; the parameters of the vulcanization treatment are as follows: vulcanization temperature 150-170° C., vulcanization time 10-20 min, pressure 12-18 MPa.

[0015] The present invention also provides an application of the low-temperature, high-elasticity, UV-resistant rubber pad, specifically: applying the rubber pad to a railway line.

[0016] The working principle and beneficial effects of the present invention are: 1. The present invention adopts natural rubber, butadiene rubber and EPDM as main components, wherein the low temperature performance of natural rubber is poor, but the elasticity is good; butadiene rubber has excellent low temperature performance; EPDM has excellent aging performance, and the three blends can complement each other; at the same time, the present invention improves the problem of poor vulcanization compatibility between EPDM and the other two rubbers through a staged mixing process and a compound vulcanization system (sulfur and peroxide composite vulcanization); at the same time, the raw material formula adopts a precise material ratio, so that the static stiffness of the rubber pad at room temperature is 37-38kN / mm, and at low temperature, the low temperature characteristics of butadiene rubber are manifested, so that the static stiffness change rate of the rubber pad at -50℃ / 23℃ is smaller, and the influence of the low temperature environment on the elasticity of the rubber pad is reduced; Rubber pads are inevitably exposed to sunlight in actual use, which will cause photo-oxidation and ultraviolet aging. Photo-oxidation aging caused by ultraviolet rays and oxygen will gradually change the color of rubber, reduce its physical and mechanical properties, and cause embrittlement. Photo-oxidation and ultraviolet rays are a process of free radical transformation and combination. First, the oxygen content in the polymer chain increases, and then the main chain breaks due to oxidation. Especially in plateau areas with high altitude (ultraviolet rays increase by about 1.3% for every 100 meters increase in altitude), the air is thin, the air transparency is high, and the ultraviolet radiation is blocked less, so the impact of ultraviolet rays on rubber pads is more obvious. The present invention adds 2-(2'-hydroxy-3',5'-di-tert-pentylphenyl)benzotriazole to the rubber, thereby increasing the protective ability of the rubber product against ultraviolet rays, and can significantly reduce the generation of aging and cracks after ultraviolet irradiation when combined with 4.4'-bis(α,α-dimethylbenzyl)diphenylamine, thereby extending the service life of the rubber pad; when the silane coupling agent Si75, 4,4'-bis(α,α-dimethylbenzyl)diphenylamine and 2-(2'-hydroxy-3',5'-di-tert-pentylphenyl)benzotriazole are used together, they can produce a synergistic effect, further improving the anti-aging performance of the rubber: the silane coupling agent enhances the stability of the internal structure of the rubber, the 4.4'-bis(α,α-dimethylbenzyl)diphenylamine inhibits the oxidation reaction, and the 2-(2'-hydroxy-3',5'-di-tert-pentylphenyl)benzotriazole prevents photo-oxidative degradation. The three additives provide comprehensive protection for the rubber from different angles.

[0017] 2. In order to further improve the UV aging resistance of the rubber pad, the present invention also provides a coating film coated on the surface of the rubber product, which has good UV aging resistance and reduces the external environmental interference to the pad to a certain extent. Compared with the existing coating film formula, the coating film provided by the present invention has better adhesion and stronger UV aging resistance. DETAILED DESCRIPTION

[0018] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0019] The materials used in the present invention can all be purchased from the market. In the following embodiments and comparative examples, the brand of natural rubber is RSS3, the brand of butadiene rubber is BR9000, the brand of ethylene propylene diene monomer rubber is EPDM4045, the brand of phenolic resin is 2402 phenolic resin, the kaolin particle size of 0-2 μm accounts for 85.40%, and the talc powder is 1000 mesh.

[0020] Example 1 (1) A low-temperature, high-elastic, UV-resistant rubber pad, the raw materials of which include 40 parts of component I, 40 parts of component II and 20 parts of component III; Component I, by mass, includes 100 parts of natural rubber, 5 parts of zinc oxide, 1.5 parts of stearic acid, 20 parts of carbon black N550, 30 parts of kaolin, 20 parts of aluminum silicate, 10 parts of talc, 3 parts of silane coupling agent Si75, 8 parts of 2-(2′-hydroxy-3′,5′-di-tert-pentylphenyl)benzotriazole, 3.5 parts of 4,4′-bis(α,α-dimethylbenzyl)diphenylamine, 3 parts of antioxidant RD, 3 parts of antioxidant H71, 0.8 parts of accelerator DTDM, 1.5 parts of accelerator CZ, 3 parts of masterbatch S-80, and 0.5 parts of DCP; Component II, by mass, includes 100 parts of butadiene rubber, 4 parts of zinc oxide, 1.5 parts of stearic acid, 15 parts of carbon black N550, 25 parts of kaolin, 15 parts of aluminum silicate, 10 parts of talc, 2 parts of silane coupling agent Si75, 8 parts of 2-(2′-hydroxy-3′,5′-di-tert-pentylphenyl)benzotriazole, 3.5 parts of 4,4′-bis(α,α-dimethylbenzyl)diphenylamine, 3 parts of antioxidant RD, 3 parts of antioxidant H71, 0.8 parts of accelerator DTDM, 1.5 parts of accelerator CZ, 2 parts of masterbatch S-80, and 0.5 parts of DCP; Component III, by mass, includes 100 parts of EPDM rubber, 3 parts of zinc oxide, 1.5 parts of stearic acid, 10 parts of carbon black N550, 20 parts of kaolin, 5 parts of aluminum silicate, 5 parts of talc, 4 parts of silane coupling agent Si75, 8 parts of 2-(2′-hydroxy-3′,5′-di-tert-pentylphenyl)benzotriazole, 3.5 parts of 4,4′-bis(α,α-dimethylbenzyl)diphenylamine, 3 parts of antioxidant RD, 3 parts of antioxidant H71, 0.8 parts of accelerator DTDM, 1.5 parts of accelerator CZ, 3 parts of masterbatch S-80, and 0.5 parts of DCP; (2) A method for preparing a low-temperature, high-elasticity, UV-resistant rubber pad, comprising the following steps: A. Mix components I to III separately: The mixing method of component I comprises the following steps: adding raw rubber into an internal mixer, and sequentially adding zinc oxide, stearic acid, filler, silane coupling agent, 2-(2′-hydroxy-3′,5′-di-tert-pentylphenyl)benzotriazole, 4,4′-bis(α,α-dimethylbenzyl)diphenylamine, antioxidant, accelerator, masterbatch S-80 and DCP to obtain a mixed rubber, wherein the mixing temperature is 90° C., the rotation speed is 30 rpm, and the mixing time is 9 minutes; the mixing method of component II and component III is the same as that of component I; B. Put the mixed rubber obtained from components I-III into an internal mixer for mixing at a mixing temperature of 90°C and a rotation speed of 30 rpm for 6 minutes; C. Add the mixed rubber obtained in step B into an open rubber mixer, use the default roller speed, adjust the roller distance to the minimum, pass cooling water, control the roller temperature to be no higher than 75° C., mix the rubber in the mixer, sheet the rubber for 3 times, make triangle packages for 5 times to obtain a film, park it for 12 hours, and then extrude it into a film using a cold feed extruder; D. Place the formed film obtained in step C in a flat vulcanizer for vulcanization treatment; the vulcanization treatment parameters are as follows: vulcanization temperature 160° C., vulcanization time 15 min, pressure 15 MPa.

[0021] (3) The surface coating of the rubber pad: The raw materials of the coating film include 100 parts of EPDM rubber, 5 parts of MgO, 2 parts of stearic acid, 60 parts of phenolic resin, 30 parts of carbon black N330, 10 parts of 2-(2′-hydroxy-3′,5′-di-tert-pentylphenyl)benzotriazole, 5 parts of 4,4′-bis(α,α-dimethylbenzyl)diphenylamine, 2 parts of accelerator PZ (zinc dimethyldithiocarbamate), 1.5 parts of sulfur, and 0.5 parts of DCP (diisopropylbenzene peroxide). The method for preparing the coating film comprises the following steps: Cut the EPDM rubber into small pieces of 2 mm; add the cut EPDM and other raw materials into cyclohexane and continue stirring for 8 hours to obtain a solution, wherein the amount of cyclohexane is: 1 g of the raw material is dissolved in 20 ml of cyclohexane; The obtained solution was poured into a rubber mill and ground for 30 minutes to obtain a coating solution, wherein the parameters of the rubber mill were as follows: voltage 380V, power 1.1kw, rotation speed 2000rpm, emulsification fineness 30μm.

[0022] The coating method of the coating solution comprises the following steps: All surfaces of the obtained pad (including the upper and lower surfaces and four sides) are coated with a coating thickness of 0.3 mm and a coating amount of 1.1 g / cm 2 , dry at room temperature for 2h; The pad surface was heated at 170° C. for 2 min using a thermal device to solidify the pad surface to obtain a product.

[0023] Example 2 (1) A low-temperature, high-elastic, UV-resistant rubber pad, the raw materials of which include 50 parts of component I, 30 parts of component II and 20 parts of component III; Component I, by mass, includes 100 parts of natural rubber, 3 parts of zinc oxide, 1.5 parts of stearic acid, 20 parts of carbon black N550, 20 parts of kaolin, 20 parts of aluminum silicate, 5 parts of talc, 4 parts of silane coupling agent Si75, 5 parts of 2-(2′-hydroxy-3′,5′-di-tert-pentylphenyl)benzotriazole, 3.5 parts of 4,4′-bis(α,α-dimethylbenzyl)diphenylamine, 3 parts of antioxidant RD, 3 parts of antioxidant H71, 0.8 parts of accelerator DTDM, 1.5 parts of accelerator CZ, 3 parts of masterbatch S-80, and 0.3 parts of DCP; Component II, by mass, includes 100 parts of butadiene rubber, 5 parts of zinc oxide, 1.5 parts of stearic acid, 10 parts of carbon black N550, 30 parts of kaolin, 5 parts of aluminum silicate, 10 parts of talc, 1 part of silane coupling agent Si75, 10 parts of 2-(2′-hydroxy-3′,5′-di-tert-pentylphenyl)benzotriazole, 3.5 parts of 4,4′-bis(α,α-dimethylbenzyl)diphenylamine, 3 parts of antioxidant RD, 3 parts of antioxidant H71, 0.8 parts of accelerator DTDM, 1.5 parts of accelerator CZ, 2 parts of masterbatch S-80, and 0.7 parts of DCP; Component III, by mass, includes 100 parts of EPDM rubber, 3 parts of zinc oxide, 1.5 parts of stearic acid, 20 parts of carbon black N550, 20 parts of kaolin, 20 parts of aluminum silicate, 5 parts of talc, 4 parts of silane coupling agent Si75, 5 parts of 2-(2′-hydroxy-3′,5′-di-tert-pentylphenyl)benzotriazole, 3.5 parts of 4,4′-bis(α,α-dimethylbenzyl)diphenylamine, 3 parts of antioxidant RD, 3 parts of antioxidant H71, 0.8 parts of accelerator DTDM, 1.5 parts of accelerator CZ, 3 parts of masterbatch S-80, and 0.3 parts of DCP; (2) A method for preparing a low-temperature, high-elasticity, UV-resistant rubber pad, comprising the following steps: A. Mix components I to III separately: The mixing method of component I comprises the following steps: adding raw rubber into an internal mixer, adding zinc oxide, stearic acid, filler, silane coupling agent, 2-(2′-hydroxy-3′,5′-di-tert-pentylphenyl)benzotriazole, 4,4′-bis(α,α-dimethylbenzyl)diphenylamine, antioxidant, accelerator, masterbatch S-80 and DCP to obtain a mixed rubber, wherein the mixing temperature is 100° C., the rotation speed is 20 rpm, and the mixing time is 12 minutes; the mixing method of component II and component III is the same as that of component I; B. Put the mixed rubber obtained from component I to component III into an internal mixer for mixing at a mixing temperature of 85°C and a rotation speed of 40 rpm for 3 minutes; C. Add the rubber mix obtained in step B into an open rubber mixer, use the default roller speed, adjust the roller distance to the minimum, pass cooling water, control the roller temperature to be no higher than 75° C., mix the rubber in the mixer, sheet the rubber for 5 times, make triangle packages for 3 times to obtain a film, and extrude it into a film by a cold feed extruder after parking it for 12 hours; D. Place the formed film obtained in step C in a flat vulcanizer for vulcanization treatment; the vulcanization treatment parameters are as follows: vulcanization temperature 170° C., vulcanization time 10 min, pressure 18 MPa.

[0024] (3) The surface coating of the rubber pad: The raw materials of the coating film include, by weight, 100 parts of EPDM rubber, 4 parts of MgO, 3 parts of stearic acid, 55 parts of phenolic resin, 35 parts of carbon black N330, 8 parts of 2-(2′-hydroxy-3′,5′-di-tert-pentylphenyl)benzotriazole, 6 parts of 4,4′-bis(α,α-dimethylbenzyl)diphenylamine, 1.5 parts of accelerator PZ, 2 parts of sulfur, and 0.4 parts of DCP; The method for preparing the coating film comprises the following steps: Cut the EPDM rubber into small pieces of 3 mm; add the cut EPDM and other raw materials into cyclohexane and continue stirring for 8 hours to obtain a solution, wherein the amount of cyclohexane is: 1 g of the raw material is dissolved in 20 ml of cyclohexane; The obtained solution was poured into a rubber mill and ground for 25 minutes to obtain a coating solution, wherein the parameters of the rubber mill were as follows: voltage 380V, power 1.1kw, rotation speed 2500rpm, emulsification fineness 25μm.

[0025] The coating method of the coating solution comprises the following steps: Coat the four sides of the obtained pad with a coating thickness of 0.2 mm and a coating amount of 1.2 g / cm 2 , dry at room temperature for 1.5h; The coated side of the pad was heated at 180° C. for 1.5 min using a thermal device to cure the side of the pad to obtain a product.

[0026] Example 3 (1) A low-temperature, high-elastic, UV-resistant rubber pad, the raw materials of which include 60 parts of component I, 20 parts of component II and 20 parts of component III; Component I, by mass, includes 100 parts of natural rubber, 5 parts of zinc oxide, 1.5 parts of stearic acid, 10 parts of carbon black N550, 30 parts of kaolin, 5 parts of aluminum silicate, 10 parts of talc, 1 part of silane coupling agent Si75, 10 parts of 2-(2′-hydroxy-3′,5′-di-tert-pentylphenyl)benzotriazole, 3.5 parts of 4,4′-bis(α,α-dimethylbenzyl)diphenylamine, 3 parts of antioxidant RD, 3 parts of antioxidant H71, 0.8 parts of accelerator DTDM, 1.5 parts of accelerator CZ, 2 parts of masterbatch S-80, and 0.7 parts of DCP; Component II, by mass, includes 100 parts of butadiene rubber, 3 parts of zinc oxide, 1.5 parts of stearic acid, 20 parts of carbon black N550, 20 parts of kaolin, 20 parts of aluminum silicate, 5 parts of talc, 4 parts of silane coupling agent Si75, 5 parts of 2-(2′-hydroxy-3′,5′-di-tert-pentylphenyl)benzotriazole, 3.5 parts of 4,4′-bis(α,α-dimethylbenzyl)diphenylamine, 3 parts of antioxidant RD, 3 parts of antioxidant H71, 0.8 parts of accelerator DTDM, 1.5 parts of accelerator CZ, 3 parts of masterbatch S-80, and 0.3 parts of DCP; Component III, by mass, includes 100 parts of EPDM rubber, 5 parts of zinc oxide, 1.5 parts of stearic acid, 10 parts of carbon black N550, 30 parts of kaolin, 5 parts of aluminum silicate, 10 parts of talc, 1 part of silane coupling agent Si75, 10 parts of 2-(2′-hydroxy-3′,5′-di-tert-pentylphenyl)benzotriazole, 3.5 parts of 4,4′-bis(α,α-dimethylbenzyl)diphenylamine, 3 parts of antioxidant RD, 3 parts of antioxidant H71, 0.8 parts of accelerator DTDM, 1.5 parts of accelerator CZ, 2 parts of masterbatch S-80, and 0.7 parts of DCP; (2) A method for preparing a low-temperature, high-elasticity, UV-resistant rubber pad, comprising the following steps: A. Mix components I to III separately: The mixing method of component I comprises the following steps: adding raw rubber into an internal mixer, adding zinc oxide, stearic acid, filler, silane coupling agent, 2-(2′-hydroxy-3′,5′-di-tert-pentylphenyl)benzotriazole, 4,4′-bis(α,α-dimethylbenzyl)diphenylamine, antioxidant, accelerator, masterbatch S-80 and DCP to obtain a mixed rubber, wherein the mixing temperature is 85° C., the rotation speed is 40 rpm, and the mixing time is 8 minutes; the mixing method of component II and component III is the same as that of component I; B. Put the mixed rubber obtained from component I to component III into an internal mixer for mixing at a mixing temperature of 100°C and a rotation speed of 20 rpm for 8 minutes; C. Add the mixed rubber obtained in step B into an open rubber mixer, use the default roller speed, adjust the roller distance to the minimum, pass cooling water, control the roller temperature to be no higher than 75° C., mix the rubber in the mixer, sheet the rubber for 3 times, make triangle packages for 5 times to obtain a film, park it for 12 hours, and then extrude it into a film using a cold feed extruder; D. Put the formed film obtained in step C into a flat vulcanizer for vulcanization treatment; the parameters of the vulcanization treatment are as follows: vulcanization temperature is 150° C., vulcanization time is 20 min, and pressure is 12 MPa.

[0027] (3) The surface coating of the rubber pad: The raw materials of the coating film include, by weight, 100 parts of EPDM rubber, 6 parts of MgO, 1 part of stearic acid, 65 parts of phenolic resin, 25 parts of carbon black N330, 12 parts of 2-(2′-hydroxy-3′,5′-di-tert-pentylphenyl)benzotriazole, 4 parts of 4,4′-bis(α,α-dimethylbenzyl)diphenylamine, 2.5 parts of accelerator PZ, 1 part of sulfur, and 0.6 parts of DCP; The method for preparing the coating film comprises the following steps: Cut the EPDM rubber into small pieces of 1 mm; add the cut EPDM and other raw materials into cyclohexane and continue stirring for 8 hours to obtain a solution, wherein the amount of cyclohexane is: 1 g of the raw material is dissolved in 20 ml of cyclohexane; The obtained solution was poured into a rubber mill and ground for 35 minutes to obtain a coating solution, wherein the parameters of the rubber mill were as follows: voltage 380 V, power 1.1 kW, rotation speed 1500 rpm, and emulsification fineness 35 μm.

[0028] The coating method of the coating solution comprises the following steps: Coat the four sides of the obtained pad with a coating thickness of 0.4 mm and a coating amount of 1.0 g / cm 2 , dry at room temperature for 3h; The side of the pad was heated at 160° C. for 3 minutes using a thermal device to solidify the side of the pad to obtain a product.

[0029] Example 4 (1) A low-temperature, high-elastic, UV-resistant rubber pad, the raw materials of which include 40 parts of component I, 40 parts of component II and 20 parts of component III; Component I, by mass, includes 100 parts of natural rubber, 5 parts of zinc oxide, 1.5 parts of stearic acid, 20 parts of carbon black N550, 30 parts of kaolin, 20 parts of aluminum silicate, 10 parts of talc, 3 parts of silane coupling agent Si75, 8 parts of 2-(2′-hydroxy-3′,5′-di-tert-pentylphenyl)benzotriazole, 3.5 parts of 4,4′-bis(α,α-dimethylbenzyl)diphenylamine, 3 parts of antioxidant RD, 3 parts of antioxidant H71, 0.8 parts of accelerator DTDM, 1.5 parts of accelerator CZ, 3 parts of masterbatch S-80, and 0.5 parts of DCP; Component II, by mass, includes 100 parts of butadiene rubber, 4 parts of zinc oxide, 1.5 parts of stearic acid, 15 parts of carbon black N550, 25 parts of kaolin, 15 parts of aluminum silicate, 10 parts of talc, 2 parts of silane coupling agent Si75, 8 parts of 2-(2′-hydroxy-3′,5′-di-tert-pentylphenyl)benzotriazole, 3.5 parts of 4,4′-bis(α,α-dimethylbenzyl)diphenylamine, 3 parts of antioxidant RD, 3 parts of antioxidant H71, 0.8 parts of accelerator DTDM, 1.5 parts of accelerator CZ, 2 parts of masterbatch S-80, and 0.5 parts of DCP; Component III, by mass, includes 100 parts of EPDM rubber, 3 parts of zinc oxide, 1.5 parts of stearic acid, 10 parts of carbon black N550, 20 parts of kaolin, 5 parts of aluminum silicate, 5 parts of talc, 4 parts of silane coupling agent Si75, 8 parts of 2-(2′-hydroxy-3′,5′-di-tert-pentylphenyl)benzotriazole, 3.5 parts of 4,4′-bis(α,α-dimethylbenzyl)diphenylamine, 3 parts of antioxidant RD, 3 parts of antioxidant H71, 0.8 parts of accelerator DTDM, 1.5 parts of accelerator CZ, 3 parts of masterbatch S-80, and 0.5 parts of DCP; (2) A method for preparing a low-temperature, high-elasticity, UV-resistant rubber pad, comprising the following steps: A. Mix components I to III separately: The mixing method of component I comprises the following steps: adding raw rubber into an internal mixer, and sequentially adding zinc oxide, stearic acid, filler, silane coupling agent, 2-(2′-hydroxy-3′,5′-di-tert-pentylphenyl)benzotriazole, 4,4′-bis(α,α-dimethylbenzyl)diphenylamine, antioxidant, accelerator, masterbatch S-80 and DCP to obtain a mixed rubber, wherein the mixing temperature is 90° C., the rotation speed is 30 rpm, and the mixing time is 9 minutes; the mixing method of component II and component III is the same as that of component I; B. Put the mixed rubber obtained from components I-III into an internal mixer for mixing at a mixing temperature of 90°C and a rotation speed of 30 rpm for 6 minutes; C. Add the mixed rubber obtained in step B into an open rubber mixer, use the default roller speed, adjust the roller distance to the minimum, pass cooling water, control the roller temperature to be no higher than 75° C., mix the rubber in the mixer, sheet the rubber for 3 times, make triangle packages for 5 times to obtain a film, park it for 12 hours, and then extrude it into a film using a cold feed extruder; D. Place the formed film obtained in step C in a flat vulcanizer for vulcanization treatment; the vulcanization treatment parameters are as follows: vulcanization temperature 160° C., vulcanization time 15 min, pressure 15 MPa.

[0030] Comparative Example 1 (1) A low-temperature, high-elastic, UV-resistant rubber pad, the raw materials of which include 40 parts of component I, 40 parts of component II and 20 parts of component III; Component I, by mass, includes 100 parts of natural rubber, 5 parts of zinc oxide, 1.5 parts of stearic acid, 20 parts of carbon black N550, 30 parts of kaolin, 20 parts of aluminum silicate, 10 parts of talc, 3 parts of silane coupling agent Si75, 3.5 parts of 4,4′-bis(α,α-dimethylbenzyl)diphenylamine, 3 parts of antioxidant RD, 3 parts of antioxidant H71, 0.8 parts of accelerator DTDM, 1.5 parts of accelerator CZ, 3 parts of masterbatch S-80, and 0.5 parts of DCP; Component II, by mass, includes 100 parts of butadiene rubber, 4 parts of zinc oxide, 1.5 parts of stearic acid, 15 parts of carbon black N550, 25 parts of kaolin, 15 parts of aluminum silicate, 10 parts of talc, 2 parts of silane coupling agent Si75, 3.5 parts of 4,4′-bis(α,α-dimethylbenzyl)diphenylamine, 3 parts of antioxidant RD, 3 parts of antioxidant H71, 0.8 parts of accelerator DTDM, 1.5 parts of accelerator CZ, 2 parts of masterbatch S-80, and 0.5 parts of DCP; Component III, by mass, includes 100 parts of EPDM rubber, 3 parts of zinc oxide, 1.5 parts of stearic acid, 10 parts of carbon black N550, 20 parts of kaolin, 5 parts of aluminum silicate, 5 parts of talc, 4 parts of silane coupling agent Si75, 3.5 parts of 4,4′-bis(α,α-dimethylbenzyl)diphenylamine, 3 parts of antioxidant RD, 3 parts of antioxidant H71, 0.8 parts of accelerator DTDM, 1.5 parts of accelerator CZ, 3 parts of masterbatch S-80, and 0.5 parts of DCP; (2) A method for preparing a low-temperature, high-elasticity, UV-resistant rubber pad, comprising the following steps: A. Mix components I to III separately: The mixing method of component I comprises the following steps: adding raw rubber into an internal mixer, and sequentially adding zinc oxide, stearic acid, filler, silane coupling agent, 4,4′-bis(α,α-dimethylbenzyl)diphenylamine, antioxidant, accelerator, masterbatch S-80 and DCP to obtain a mixed rubber, wherein the mixing temperature is 90° C., the rotation speed is 30 rpm, and the mixing time is 9 minutes; the mixing method of component II and component III is the same as that of component I; B. Put the mixed rubber obtained from components I-III into an internal mixer for mixing at a mixing temperature of 90°C and a rotation speed of 30 rpm for 6 minutes; C. Add the mixed rubber obtained in step B into an open rubber mixer, use the default roller speed, adjust the roller distance to the minimum, pass cooling water, control the roller temperature to be no higher than 75° C., mix the rubber in the mixer, sheet the rubber for 3 times, make triangle packages for 5 times to obtain a film, park it for 12 hours, and then extrude it into a film using a cold feed extruder; D. Place the formed film obtained in step C in a flat vulcanizer for vulcanization treatment; the vulcanization treatment parameters are as follows: vulcanization temperature 160° C., vulcanization time 15 min, pressure 15 MPa.

[0031] Comparative Example 2 (1) A low-temperature, high-elastic, UV-resistant rubber pad, the raw materials of which include 40 parts of component I, 40 parts of component II and 20 parts of component III; Component I, by mass, includes 100 parts of natural rubber, 5 parts of zinc oxide, 1.5 parts of stearic acid, 20 parts of carbon black N550, 30 parts of kaolin, 20 parts of aluminum silicate, 10 parts of talc, 3 parts of silane coupling agent Si75, 8 parts of 2-(2′-hydroxy-3′,5′-di-tert-pentylphenyl)benzotriazole, 3 parts of antioxidant RD, 3 parts of antioxidant H71, 0.8 parts of accelerator DTDM, 1.5 parts of accelerator CZ, 3 parts of masterbatch S-80, and 0.5 parts of DCP; Component II, by mass, includes 100 parts of butadiene rubber, 4 parts of zinc oxide, 1.5 parts of stearic acid, 15 parts of carbon black N550, 25 parts of kaolin, 15 parts of aluminum silicate, 10 parts of talc, 2 parts of silane coupling agent Si75, 8 parts of 2-(2′-hydroxy-3′,5′-di-tert-pentylphenyl)benzotriazole, 3 parts of antioxidant RD, 3 parts of antioxidant H71, 0.8 parts of accelerator DTDM, 1.5 parts of accelerator CZ, 2 parts of masterbatch S-80, and 0.5 parts of DCP; Component III, by mass, includes 100 parts of EPDM rubber, 3 parts of zinc oxide, 1.5 parts of stearic acid, 10 parts of carbon black N550, 20 parts of kaolin, 5 parts of aluminum silicate, 5 parts of talc, 4 parts of silane coupling agent Si75, 8 parts of 2-(2′-hydroxy-3′,5′-di-tert-pentylphenyl)benzotriazole, 3 parts of antioxidant RD, 3 parts of antioxidant H71, 0.8 parts of accelerator DTDM, 1.5 parts of accelerator CZ, 3 parts of masterbatch S-80, and 0.5 parts of DCP; (2) A method for preparing a low-temperature, high-elasticity, UV-resistant rubber pad, comprising the following steps: A. Mix components I to III separately: The mixing method of component I comprises the following steps: adding raw rubber into an internal mixer, and sequentially adding zinc oxide, stearic acid, filler, silane coupling agent, 2-(2′-hydroxy-3′,5′-di-tert-pentylphenyl)benzotriazole, antioxidant, accelerator, masterbatch S-80 and DCP to obtain a mixed rubber, wherein the mixing temperature is 90° C., the rotation speed is 30 rpm, and the mixing time is 9 minutes; the mixing method of component II and component III is the same as that of component I; B. Put the mixed rubber obtained from components I-III into an internal mixer for mixing at a mixing temperature of 90°C and a rotation speed of 30 rpm for 6 minutes; C. Add the mixed rubber obtained in step B into an open rubber mixer, use the default roller speed, adjust the roller distance to the minimum, pass cooling water, control the roller temperature to be no higher than 75° C., mix the rubber in the mixer, sheet the rubber for 3 times, make triangle packages for 5 times to obtain a film, park it for 12 hours, and then extrude it into a film using a cold feed extruder; D. Place the formed film obtained in step C in a flat vulcanizer for vulcanization treatment; the vulcanization treatment parameters are as follows: vulcanization temperature 160° C., vulcanization time 15 min, pressure 15 MPa.

[0032] Comparative Example 3 (1) A low-temperature, high-elastic, UV-resistant rubber pad, the raw materials of which include 40 parts of component I, 40 parts of component II and 20 parts of component III; Component I, by mass, includes 100 parts of natural rubber, 5 parts of zinc oxide, 1.5 parts of stearic acid, 20 parts of carbon black N550, 30 parts of kaolin, 20 parts of aluminum silicate, 10 parts of talc, 3 parts of silane coupling agent Si75, 8 parts of 2-(2′-hydroxy-3′,5′-di-tert-amylphenyl)benzotriazole, 3.5 parts of antioxidant KY-405, 3 parts of antioxidant RD, 3 parts of antioxidant H71, 0.8 parts of accelerator DTDM, 1.5 parts of accelerator CZ, 3 parts of masterbatch S-80, and 0.5 parts of DCP; Component II, by mass, includes 100 parts of butadiene rubber, 4 parts of zinc oxide, 1.5 parts of stearic acid, 15 parts of carbon black N550, 25 parts of kaolin, 15 parts of aluminum silicate, 10 parts of talc, 2 parts of silane coupling agent Si75, 8 parts of 2-(2′-hydroxy-3′,5′-di-tert-pentylphenyl)benzotriazole, 3.5 parts of antioxidant KY-405, 3 parts of antioxidant RD, 3 parts of antioxidant H71, 0.8 parts of accelerator DTDM, 1.5 parts of accelerator CZ, 2 parts of masterbatch S-80, and 0.5 parts of DCP; Component III, by mass, includes 100 parts of EPDM rubber, 3 parts of zinc oxide, 1.5 parts of stearic acid, 10 parts of carbon black N550, 20 parts of kaolin, 5 parts of aluminum silicate, 5 parts of talc, 4 parts of silane coupling agent Si75, 8 parts of 2-(2′-hydroxy-3′,5′-di-tert-pentylphenyl)benzotriazole, 3.5 parts of antioxidant KY-405, 3 parts of antioxidant RD, 3 parts of antioxidant H71, 0.8 parts of accelerator DTDM, 1.5 parts of accelerator CZ, 3 parts of masterbatch S-80, and 0.5 parts of DCP; (2) A method for preparing a low-temperature, high-elasticity, UV-resistant rubber pad, comprising the following steps: A. Mix components I to III separately: The mixing method of component I comprises the following steps: adding raw rubber into an internal mixer, and sequentially adding zinc oxide, stearic acid, filler, silane coupling agent, 2-(2′-hydroxy-3′,5′-di-tert-pentylphenyl)benzotriazole, antioxidant KY-405, antioxidant, accelerator, masterbatch S-80 and DCP to obtain a mixed rubber, wherein the mixing temperature is 90° C., the rotation speed is 30 rpm, and the mixing time is 9 minutes; the mixing method of component II and component III is the same as that of component I; B. Put the mixed rubber obtained from components I-III into an internal mixer for mixing at a mixing temperature of 90°C and a rotation speed of 30 rpm for 6 minutes; C. Add the mixed rubber obtained in step B into an open rubber mixer, use the default roller speed, adjust the roller distance to the minimum, pass cooling water, control the roller temperature to be no higher than 75° C., mix the rubber in the mixer, sheet the rubber for 3 times, make triangle packages for 5 times to obtain a film, park it for 12 hours, and then extrude it into a film using a cold feed extruder; D. Place the formed film obtained in step C in a flat vulcanizer for vulcanization treatment; the vulcanization treatment parameters are as follows: vulcanization temperature 160° C., vulcanization time 15 min, pressure 15 MPa.

[0033] Comparative Example 4 (1) A low-temperature, high-elastic, UV-resistant rubber pad, the raw materials of which include 40 parts of component I, 40 parts of component II and 20 parts of component III; Component I, by mass, includes 100 parts of natural rubber, 5 parts of zinc oxide, 1.5 parts of stearic acid, 20 parts of carbon black N550, 30 parts of kaolin, 20 parts of aluminum silicate, 10 parts of talc, 3 parts of silane coupling agent Si75, 3 parts of antioxidant RD, 3 parts of antioxidant H71, 0.8 parts of accelerator DTDM, 1.5 parts of accelerator CZ, 3 parts of masterbatch S-80, and 0.5 parts of DCP; Component II, by mass, includes 100 parts of butadiene rubber, 4 parts of zinc oxide, 1.5 parts of stearic acid, 15 parts of carbon black N550, 25 parts of kaolin, 15 parts of aluminum silicate, 10 parts of talc, 2 parts of silane coupling agent Si75, 3 parts of antioxidant RD, 3 parts of antioxidant H71, 0.8 parts of accelerator DTDM, 1.5 parts of accelerator CZ, 2 parts of masterbatch S-80, and 0.5 parts of DCP; Component III, by mass, includes 100 parts of EPDM rubber, 3 parts of zinc oxide, 1.5 parts of stearic acid, 10 parts of carbon black N550, 20 parts of kaolin, 5 parts of aluminum silicate, 5 parts of talc, 4 parts of silane coupling agent Si75, 3 parts of antioxidant RD, 3 parts of antioxidant H71, 0.8 parts of accelerator DTDM, 1.5 parts of accelerator CZ, 3 parts of masterbatch S-80, and 0.5 parts of DCP; (2) A method for preparing a low-temperature, high-elasticity, UV-resistant rubber pad, comprising the following steps: A. Mix components I to III separately: The mixing method of component I comprises the following steps: adding raw rubber into an internal mixer, and sequentially adding zinc oxide, stearic acid, filler, silane coupling agent, antioxidant, accelerator, masterbatch S-80 and DCP to obtain a mixed rubber, wherein the mixing temperature is 90° C., the rotation speed is 30 rpm, and the mixing time is 9 minutes; the mixing method of component II and component III is the same as that of component I; B. Put the mixed rubber obtained from components I-III into an internal mixer for mixing at a mixing temperature of 90°C and a rotation speed of 30 rpm for 6 minutes; C. Add the mixed rubber obtained in step B into an open rubber mixer, use the default roller speed, adjust the roller distance to the minimum, pass cooling water, control the roller temperature to be no higher than 75° C., mix the rubber in the mixer, sheet the rubber for 3 times, make triangle packages for 5 times to obtain a film, park it for 12 hours, and then extrude it into a film using a cold feed extruder; D. Place the formed film obtained in step C in a flat vulcanizer for vulcanization treatment; the vulcanization treatment parameters are as follows: vulcanization temperature 160° C., vulcanization time 15 min, pressure 15 MPa.

[0034] Comparative Example 5 (1) A low-temperature, high-elastic, UV-resistant rubber pad, the raw materials of which include 40 parts of component I, 40 parts of component II and 20 parts of component III; Component I, by mass, includes 100 parts of natural rubber, 5 parts of zinc oxide, 1.5 parts of stearic acid, 20 parts of carbon black N550, 30 parts of kaolin, 20 parts of aluminum silicate, 10 parts of talc, 3 parts of silane coupling agent Si75, 8 parts of 2-(2′-hydroxy-3′,5′-di-tert-pentylphenyl)benzotriazole, 3.5 parts of 4,4′-bis(α,α-dimethylbenzyl)diphenylamine, 3 parts of antioxidant RD, 3 parts of antioxidant H71, 0.8 parts of accelerator DTDM, 1.5 parts of accelerator CZ, 3 parts of masterbatch S-80, and 0.5 parts of DCP; Component II, by mass, includes 100 parts of butadiene rubber, 4 parts of zinc oxide, 1.5 parts of stearic acid, 15 parts of carbon black N550, 25 parts of kaolin, 15 parts of aluminum silicate, 10 parts of talc, 2 parts of silane coupling agent Si75, 8 parts of 2-(2′-hydroxy-3′,5′-di-tert-pentylphenyl)benzotriazole, 3.5 parts of 4,4′-bis(α,α-dimethylbenzyl)diphenylamine, 3 parts of antioxidant RD, 3 parts of antioxidant H71, 0.8 parts of accelerator DTDM, 1.5 parts of accelerator CZ, 2 parts of masterbatch S-80, and 0.5 parts of DCP; Component III, by mass, includes 100 parts of EPDM rubber, 3 parts of zinc oxide, 1.5 parts of stearic acid, 10 parts of carbon black N550, 20 parts of kaolin, 5 parts of aluminum silicate, 5 parts of talc, 4 parts of silane coupling agent Si75, 8 parts of 2-(2′-hydroxy-3′,5′-di-tert-pentylphenyl)benzotriazole, 3.5 parts of 4,4′-bis(α,α-dimethylbenzyl)diphenylamine, 3 parts of antioxidant RD, 3 parts of antioxidant H71, 0.8 parts of accelerator DTDM, 1.5 parts of accelerator CZ, 3 parts of masterbatch S-80, and 0.5 parts of DCP; (2) A method for preparing a low-temperature, high-elasticity, UV-resistant rubber pad, comprising the following steps: A. Mix components I to III separately: The mixing method of component I comprises the following steps: adding raw rubber into an internal mixer, and sequentially adding zinc oxide, stearic acid, filler, silane coupling agent, 2-(2′-hydroxy-3′,5′-di-tert-pentylphenyl)benzotriazole, 4,4′-bis(α,α-dimethylbenzyl)diphenylamine, antioxidant, accelerator, masterbatch S-80 and DCP to obtain a mixed rubber, wherein the mixing temperature is 90° C., the rotation speed is 30 rpm, and the mixing time is 9 minutes; the mixing method of component II and component III is the same as that of component I; B. Put the mixed rubber obtained from components I-III into an internal mixer for mixing at a mixing temperature of 90°C and a rotation speed of 30 rpm for 6 minutes; C. Add the mixed rubber obtained in step B into an open rubber mixer, use the default roller speed, adjust the roller distance to the minimum, pass cooling water, control the roller temperature to be no higher than 75° C., mix the rubber in the mixer, sheet the rubber for 3 times, make triangle packages for 5 times to obtain a film, park it for 12 hours, and then extrude it into a film using a cold feed extruder; D. Place the formed film obtained in step C in a flat vulcanizer for vulcanization treatment; the vulcanization treatment parameters are as follows: vulcanization temperature 160° C., vulcanization time 15 min, pressure 15 MPa.

[0035] (3) The surface coating of the rubber pad: The raw materials of the coating film include, by weight, 100 parts of chloroprene rubber SN244X, 5 parts of MgO, 2 parts of stearic acid, 60 parts of phenolic resin, 30 parts of carbon black N330, 10 parts of 2-(2′-hydroxy-3′,5′-di-tert-pentylphenyl)benzotriazole, 5 parts of 4,4′-bis(α,α-dimethylbenzyl)diphenylamine, 2 parts of accelerator PZ (zinc dimethyldithiocarbamate), 1.5 parts of sulfur, and 0.5 parts of DCP (diisopropylbenzene peroxide); The method for preparing the coating film comprises the following steps: Cut chloroprene rubber SN244X into small pieces of 2 mm; add the cut EPDM and other raw materials into cyclohexane and continue stirring for 8 hours to obtain a solution, wherein the amount of cyclohexane is: 1 g of raw material is dissolved in 20 ml of cyclohexane; The obtained solution was poured into a rubber mill and ground for 30 minutes to obtain a coating solution, wherein the parameters of the rubber mill were as follows: voltage 380V, power 1.1kw, rotation speed 2000rpm, emulsification fineness 30μm.

[0036] The coating method of the coating solution comprises the following steps: All surfaces of the obtained pad (including the upper and lower surfaces and four sides) are coated with a coating thickness of 0.3 mm and a coating amount of 1.1 g / cm 2 , dry at room temperature for 2h; The pad surface was heated at 170° C. for 2 min using a thermal device to solidify the pad surface to obtain a product.

[0037] Comparative Example 6 (1) A low-temperature, high-elastic, UV-resistant rubber pad, the raw materials of which include 40 parts of component I, 40 parts of component II and 20 parts of component III; Component I, by mass, includes 100 parts of natural rubber, 5 parts of zinc oxide, 1.5 parts of stearic acid, 20 parts of carbon black N550, 30 parts of kaolin, 20 parts of aluminum silicate, 10 parts of talc, 3 parts of silane coupling agent Si75, 8 parts of 2-(2′-hydroxy-3′,5′-di-tert-pentylphenyl)benzotriazole, 3.5 parts of 4,4′-bis(α,α-dimethylbenzyl)diphenylamine, 3 parts of antioxidant RD, 3 parts of antioxidant H71, 0.8 parts of accelerator DTDM, 1.5 parts of accelerator CZ, 3 parts of masterbatch S-80, and 0.5 parts of DCP; Component II, by mass, includes 100 parts of butadiene rubber, 4 parts of zinc oxide, 1.5 parts of stearic acid, 15 parts of carbon black N550, 25 parts of kaolin, 15 parts of aluminum silicate, 10 parts of talc, 2 parts of silane coupling agent Si75, 8 parts of 2-(2′-hydroxy-3′,5′-di-tert-pentylphenyl)benzotriazole, 3.5 parts of 4,4′-bis(α,α-dimethylbenzyl)diphenylamine, 3 parts of antioxidant RD, 3 parts of antioxidant H71, 0.8 parts of accelerator DTDM, 1.5 parts of accelerator CZ, 2 parts of masterbatch S-80, and 0.5 parts of DCP; Component III, by mass, includes 100 parts of EPDM rubber, 3 parts of zinc oxide, 1.5 parts of stearic acid, 10 parts of carbon black N550, 20 parts of kaolin, 5 parts of aluminum silicate, 5 parts of talc, 4 parts of silane coupling agent Si75, 8 parts of 2-(2′-hydroxy-3′,5′-di-tert-pentylphenyl)benzotriazole, 3.5 parts of 4,4′-bis(α,α-dimethylbenzyl)diphenylamine, 3 parts of antioxidant RD, 3 parts of antioxidant H71, 0.8 parts of accelerator DTDM, 1.5 parts of accelerator CZ, 3 parts of masterbatch S-80, and 0.5 parts of DCP; (2) A method for preparing a low-temperature, high-elasticity, UV-resistant rubber pad, comprising the following steps: A. Mix components I to III separately: The mixing method of component I comprises the following steps: adding raw rubber into an internal mixer, and sequentially adding zinc oxide, stearic acid, filler, silane coupling agent, 2-(2′-hydroxy-3′,5′-di-tert-pentylphenyl)benzotriazole, 4,4′-bis(α,α-dimethylbenzyl)diphenylamine, antioxidant, accelerator, masterbatch S-80 and DCP to obtain a mixed rubber, wherein the mixing temperature is 90° C., the rotation speed is 30 rpm, and the mixing time is 9 minutes; the mixing method of component II and component III is the same as that of component I; B. Put the mixed rubber obtained from components I-III into an internal mixer for mixing at a mixing temperature of 90°C and a rotation speed of 30 rpm for 6 minutes; C. Add the mixed rubber obtained in step B into an open rubber mixer, use the default roller speed, adjust the roller distance to the minimum, pass cooling water, control the roller temperature to be no higher than 75° C., mix the rubber in the mixer, sheet the rubber for 3 times, make triangle packages for 5 times to obtain a film, park it for 12 hours, and then extrude it into a film using a cold feed extruder; D. Place the formed film obtained in step C in a flat vulcanizer for vulcanization treatment; the vulcanization treatment parameters are as follows: vulcanization temperature 160° C., vulcanization time 15 min, pressure 15 MPa.

[0038] (3) The surface coating of the rubber pad: The raw materials of the coating film include 80 parts of EPDM rubber, 5 parts of MgO, 2 parts of stearic acid, 80 parts of phenolic resin, 30 parts of carbon black N330, 10 parts of 2-(2′-hydroxy-3′,5′-di-tert-pentylphenyl)benzotriazole, 5 parts of 4,4′-bis(α,α-dimethylbenzyl)diphenylamine, 2 parts of accelerator PZ (zinc dimethyldithiocarbamate), 1.5 parts of sulfur, and 0.5 parts of DCP (diisopropylbenzene peroxide); The method for preparing the coating film comprises the following steps: Cut the EPDM rubber into small pieces of 2 mm; add the cut EPDM and other raw materials into cyclohexane and continue stirring for 8 hours to obtain a solution, wherein the amount of cyclohexane is: 1 g of the raw material is dissolved in 20 ml of cyclohexane; The obtained solution was poured into a rubber mill and ground for 30 minutes to obtain a coating solution, wherein the parameters of the rubber mill were as follows: voltage 380V, power 1.1kw, rotation speed 2000rpm, emulsification fineness 30μm.

[0039] The coating method of the coating solution comprises the following steps: All surfaces of the obtained pad (including the upper and lower surfaces and four sides) are coated with a coating thickness of 0.3 mm and a coating amount of 1.1 g / cm 2 , dry at room temperature for 2h; The pad surface was heated at 170° C. for 2 min using a thermal device to solidify the pad surface to obtain a product.

[0040] Comparative Example 7 (1) A low-temperature, high-elastic, UV-resistant rubber pad, the raw materials of which include 70 parts of component I, 10 parts of component II and 20 parts of component III; Component I, by mass, includes 100 parts of natural rubber, 5 parts of zinc oxide, 1.5 parts of stearic acid, 20 parts of carbon black N550, 30 parts of kaolin, 20 parts of aluminum silicate, 10 parts of talc, 3 parts of silane coupling agent Si75, 8 parts of 2-(2′-hydroxy-3′,5′-di-tert-pentylphenyl)benzotriazole, 3.5 parts of 4,4′-bis(α,α-dimethylbenzyl)diphenylamine, 3 parts of antioxidant RD, 3 parts of antioxidant H71, 0.8 parts of accelerator DTDM, 1.5 parts of accelerator CZ, 3 parts of masterbatch S-80, and 0.5 parts of DCP; Component II, by mass, includes 100 parts of butadiene rubber, 4 parts of zinc oxide, 1.5 parts of stearic acid, 15 parts of carbon black N550, 25 parts of kaolin, 15 parts of aluminum silicate, 10 parts of talc, 2 parts of silane coupling agent Si75, 8 parts of 2-(2′-hydroxy-3′,5′-di-tert-pentylphenyl)benzotriazole, 3.5 parts of 4,4′-bis(α,α-dimethylbenzyl)diphenylamine, 3 parts of antioxidant RD, 3 parts of antioxidant H71, 0.8 parts of accelerator DTDM, 1.5 parts of accelerator CZ, 2 parts of masterbatch S-80, and 0.5 parts of DCP; Component III, by mass, includes 100 parts of EPDM rubber, 3 parts of zinc oxide, 1.5 parts of stearic acid, 10 parts of carbon black N550, 20 parts of kaolin, 5 parts of aluminum silicate, 5 parts of talc, 4 parts of silane coupling agent Si75, 8 parts of 2-(2′-hydroxy-3′,5′-di-tert-pentylphenyl)benzotriazole, 3.5 parts of 4,4′-bis(α,α-dimethylbenzyl)diphenylamine, 3 parts of antioxidant RD, 3 parts of antioxidant H71, 0.8 parts of accelerator DTDM, 1.5 parts of accelerator CZ, 3 parts of masterbatch S-80, and 0.5 parts of DCP; (2) A method for preparing a low-temperature, high-elasticity, UV-resistant rubber pad, comprising the following steps: A. Mix components I to III separately: The mixing method of component I comprises the following steps: adding raw rubber into an internal mixer, and sequentially adding zinc oxide, stearic acid, filler, silane coupling agent, 2-(2′-hydroxy-3′,5′-di-tert-pentylphenyl)benzotriazole, 4,4′-bis(α,α-dimethylbenzyl)diphenylamine, antioxidant, accelerator, masterbatch S-80 and DCP to obtain a mixed rubber, wherein the mixing temperature is 90° C., the rotation speed is 30 rpm, and the mixing time is 9 minutes; the mixing method of component II and component III is the same as that of component I; B. Put the mixed rubber obtained from components I-III into an internal mixer for mixing at a mixing temperature of 90°C and a rotation speed of 30 rpm for 6 minutes; C. Add the mixed rubber obtained in step B into an open rubber mixer, use the default roller speed, adjust the roller distance to the minimum, pass cooling water, control the roller temperature to be no higher than 75° C., mix the rubber in the mixer, sheet the rubber for 3 times, make triangle packages for 5 times to obtain a film, park it for 12 hours, and then extrude it into a film using a cold feed extruder; D. Place the formed film obtained in step C in a flat vulcanizer for vulcanization treatment; the vulcanization treatment parameters are as follows: vulcanization temperature 160° C., vulcanization time 15 min, pressure 15 MPa.

[0041] (3) The surface coating of the rubber pad: The raw materials of the coating film include 100 parts of EPDM rubber, 5 parts of MgO, 2 parts of stearic acid, 60 parts of phenolic resin, 30 parts of carbon black N330, 10 parts of 2-(2′-hydroxy-3′,5′-di-tert-pentylphenyl)benzotriazole, 5 parts of 4,4′-bis(α,α-dimethylbenzyl)diphenylamine, 2 parts of accelerator PZ (zinc dimethyldithiocarbamate), 1.5 parts of sulfur, and 0.5 parts of DCP (diisopropylbenzene peroxide). The method for preparing the coating film comprises the following steps: Cut the EPDM rubber into small pieces of 2 mm; add the cut EPDM and other raw materials into cyclohexane and continue stirring for 8 hours to obtain a solution, wherein the amount of cyclohexane is: 1 g of the raw material is dissolved in 20 ml of cyclohexane; The obtained solution was poured into a rubber mill and ground for 30 minutes to obtain a coating solution, wherein the parameters of the rubber mill were as follows: voltage 380V, power 1.1kw, rotation speed 2000rpm, emulsification fineness 30μm.

[0042] The coating method of the coating solution comprises the following steps: All surfaces of the obtained pad (including the upper and lower surfaces and four sides) are coated with a coating thickness of 0.3 mm and a coating amount of 1.1 g / cm 2 , dry at room temperature for 2h; The pad surface was heated at 170° C. for 2 min using a thermal device to solidify the pad surface to obtain a product.

[0043] Comparative Example 8 (1) A low-temperature, high-elastic, UV-resistant rubber pad, the raw materials of which include 10 parts of component I, 70 parts of component II and 20 parts of component III; Component I, by mass, includes 100 parts of natural rubber, 5 parts of zinc oxide, 1.5 parts of stearic acid, 20 parts of carbon black N550, 30 parts of kaolin, 20 parts of aluminum silicate, 10 parts of talc, 3 parts of silane coupling agent Si75, 8 parts of 2-(2′-hydroxy-3′,5′-di-tert-pentylphenyl)benzotriazole, 3.5 parts of 4,4′-bis(α,α-dimethylbenzyl)diphenylamine, 3 parts of antioxidant RD, 3 parts of antioxidant H71, 0.8 parts of accelerator DTDM, 1.5 parts of accelerator CZ, 3 parts of masterbatch S-80, and 0.5 parts of DCP; Component II, by mass, includes 100 parts of butadiene rubber, 4 parts of zinc oxide, 1.5 parts of stearic acid, 15 parts of carbon black N550, 25 parts of kaolin, 15 parts of aluminum silicate, 10 parts of talc, 2 parts of silane coupling agent Si75, 8 parts of 2-(2′-hydroxy-3′,5′-di-tert-pentylphenyl)benzotriazole, 3.5 parts of 4,4′-bis(α,α-dimethylbenzyl)diphenylamine, 3 parts of antioxidant RD, 3 parts of antioxidant H71, 0.8 parts of accelerator DTDM, 1.5 parts of accelerator CZ, 2 parts of masterbatch S-80, and 0.5 parts of DCP; Component III, by mass, includes 100 parts of EPDM rubber, 3 parts of zinc oxide, 1.5 parts of stearic acid, 10 parts of carbon black N550, 20 parts of kaolin, 5 parts of aluminum silicate, 5 parts of talc, 4 parts of silane coupling agent Si75, 8 parts of 2-(2′-hydroxy-3′,5′-di-tert-pentylphenyl)benzotriazole, 3.5 parts of 4,4′-bis(α,α-dimethylbenzyl)diphenylamine, 3 parts of antioxidant RD, 3 parts of antioxidant H71, 0.8 parts of accelerator DTDM, 1.5 parts of accelerator CZ, 3 parts of masterbatch S-80, and 0.5 parts of DCP; (2) A method for preparing a low-temperature, high-elasticity, UV-resistant rubber pad, comprising the following steps: A. Mix components I to III separately: The mixing method of component I comprises the following steps: adding raw rubber into an internal mixer, and sequentially adding zinc oxide, stearic acid, filler, silane coupling agent, 2-(2′-hydroxy-3′,5′-di-tert-pentylphenyl)benzotriazole, 4,4′-bis(α,α-dimethylbenzyl)diphenylamine, antioxidant, accelerator, masterbatch S-80 and DCP to obtain a mixed rubber, wherein the mixing temperature is 90° C., the rotation speed is 30 rpm, and the mixing time is 9 minutes; the mixing method of component II and component III is the same as that of component I; B. Put the mixed rubber obtained from components I-III into an internal mixer for mixing at a mixing temperature of 90°C and a rotation speed of 30 rpm for 6 minutes; C. Add the mixed rubber obtained in step B into an open rubber mixer, use the default roller speed, adjust the roller distance to the minimum, pass cooling water, control the roller temperature to be no higher than 75° C., mix the rubber in the mixer, sheet the rubber for 3 times, make triangle packages for 5 times to obtain a film, park it for 12 hours, and then extrude it into a film using a cold feed extruder; D. Place the formed film obtained in step C in a flat vulcanizer for vulcanization treatment; the vulcanization treatment parameters are as follows: vulcanization temperature 160° C., vulcanization time 15 min, pressure 15 MPa.

[0044] (3) The surface coating of the rubber pad: The raw materials of the coating film include 100 parts of EPDM rubber, 5 parts of MgO, 2 parts of stearic acid, 60 parts of phenolic resin, 30 parts of carbon black N330, 10 parts of 2-(2′-hydroxy-3′,5′-di-tert-pentylphenyl)benzotriazole, 5 parts of 4,4′-bis(α,α-dimethylbenzyl)diphenylamine, 2 parts of accelerator PZ (zinc dimethyldithiocarbamate), 1.5 parts of sulfur, and 0.5 parts of DCP (diisopropylbenzene peroxide). The method for preparing the coating film comprises the following steps: Cut the EPDM rubber into small pieces of 2 mm; add the cut EPDM and other raw materials into cyclohexane and continue stirring for 8 hours to obtain a solution, wherein the amount of cyclohexane is: 1 g of the raw material is dissolved in 20 ml of cyclohexane; The obtained solution was poured into a rubber mill and ground for 30 minutes to obtain a coating solution, wherein the parameters of the rubber mill were as follows: voltage 380V, power 1.1kw, rotation speed 2000rpm, emulsification fineness 30μm.

[0045] The coating method of the coating solution comprises the following steps: All surfaces of the obtained pad (including the upper and lower surfaces and four sides) are coated with a coating thickness of 0.3 mm and a coating amount of 1.1 g / cm 2 , dry at room temperature for 2h; The pad surface was heated at 170° C. for 2 min using a thermal device to solidify the pad surface to obtain a product.

[0046] In order to better illustrate the characteristics of the pad provided by the embodiment of the present invention, the products prepared by the comparative example and the embodiment were tested for corresponding performances, and the results are shown in Table 1-2.

[0047] Table 1 Table 2 The test standards are as follows: Hardness is in accordance with GB / T 531.1; Tensile strength, elongation at break and 200% elongation stress shall comply with GB / T528; The UV aging environmental conditions adopt GB / T 14522-93; Static stiffness and low temperature static stiffness change rate shall comply with TB / T 3395.

[0048] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A low-temperature, high-elastic, UV-resistant rubber pad, characterized in that: The raw materials include component I, component II and component III in a mass ratio of 2-3:1-2:1; in component I to component III, by mass, they all include 100 parts of raw rubber, 3-5 parts of zinc oxide, 1.5 parts of stearic acid, 40-80 parts of filler, 1-4 parts of silane coupling agent Si75, 5-10 parts of 2-(2′-hydroxy-3′,5′-di-tert-pentylphenyl)benzotriazole, 3.5 parts of 4,4′-bis(α,α-dimethylbenzyl)diphenylamine, 6 parts of antioxidant, 2.3 parts of accelerator, 2-3 parts of masterbatch S-80, and 0.3-0.7 parts of DCP, wherein the raw rubber in component I, component II and component III are natural rubber, butadiene rubber and ethylene propylene diene monomer rubber, respectively.

2. The low-temperature, high-elastic, UV-resistant rubber pad according to claim 1, characterized in that: The surface of the rubber pad is coated with a coating film, and the raw materials of the coating film include, by weight, 100 parts of EPDM rubber, 4-6 parts of MgO, 1-3 parts of stearic acid, 55-65 parts of phenolic resin, 25-35 parts of carbon black N330, 8-12 parts of 2-(2'-hydroxy-3',5'-di-tert-pentylphenyl)benzotriazole, 4-6 parts of 4,4'-bis(α,α-dimethylbenzyl)diphenylamine, 1.5-2.5 parts of accelerator PZ, 1-2 parts of sulfur, and 0.4-0.6 parts of DCP.

3. The low-temperature, high-elastic, UV-resistant rubber pad according to claim 2, characterized in that: The method for preparing the coating film comprises the following steps: Cut the EPDM rubber into small pieces of 1-3 mm; add the cut EPDM and other raw materials into cyclohexane and continue stirring for 8 hours to obtain a solution, wherein the amount of cyclohexane is: 1 g of the raw material is dissolved in 20 ml of cyclohexane; The obtained solution is poured into a rubber mill and ground for 25-35 minutes to obtain a coating solution, wherein the parameters of the rubber mill are as follows: voltage 380V, power 1.1kw, rotation speed 1500-2500rpm, emulsification fineness 25-35μm.

4. The low-temperature, high-elastic, UV-resistant rubber pad according to claim 3, characterized in that: The coating method of the coating solution comprises the following steps: The coating solution is applied on the surface of the obtained rubber pad, with a coating thickness of 0.2-0.4 mm and a coating amount of 1.0-1.2 g / cm 2 , dry at room temperature for 1.5-3h; Use thermal equipment to heat the narrow edge of the pad at 160-180°C for 1.5-3 minutes to solidify the periphery of the pad to obtain the product.

5. The low-temperature, high-elastic, UV-resistant rubber pad according to claim 1, characterized in that: The brand of the natural rubber is RSS3; the brand of the butadiene rubber is BR9000; and the brand of the ethylene propylene diene monomer rubber is EPDM4045.

6. The low-temperature, high-elastic, UV-resistant rubber pad according to claim 1, characterized in that: The filler is selected from one or more of carbon black N550, white carbon black, kaolin, aluminum silicate and talc.

7. The low-temperature, high-elastic, UV-resistant rubber pad according to claim 1, characterized in that: The antioxidant is antioxidant RD and / or antioxidant H71; the accelerator is accelerator DTDM and / or accelerator CZ.

8. The low-temperature, high-elastic, UV-resistant rubber pad according to claim 1, characterized in that: The filler is composed of 10-20 parts of carbon black N550, 20-30 parts of kaolin, 5-20 parts of aluminum silicate, and 5-10 parts of talc; The antioxidant is composed of 3 parts of antioxidant RD and 3 parts of antioxidant H71; The accelerator is composed of 0.8 parts of accelerator DTDM and 1.5 parts of accelerator CZ.

9. A method for preparing a low-temperature, high-elastic, UV-resistant rubber pad according to any one of claims 1 to 8, characterized in that: The following steps are involved: A. Mix components I to III separately: The mixing method of component I comprises the following steps: adding raw rubber into an internal mixer, adding zinc oxide, stearic acid, filler, silane coupling agent, 2-(2′-hydroxy-3′,5′-di-tert-pentylphenyl)benzotriazole, 4,4′-bis(α,α-dimethylbenzyl)diphenylamine, antioxidant, accelerator, masterbatch S-80 and DCP to obtain a mixed rubber, wherein the mixing temperature is 85-100° C., the rotation speed is 20-40 rpm, and the mixing time is 8-12 minutes; the mixing method of component II and component III is the same as that of component I; B. Put the mixed rubber obtained from component I to component III into an internal mixer for mixing at a mixing temperature of 85-100°C, a rotation speed of 20-40 rpm, and mixing for 3-8 minutes; C. Add the mixed rubber obtained in step B into an open rubber mixer, use the default roller speed, adjust the roller distance to the minimum, pass cooling water, control the roller temperature to be no higher than 75° C., mix the rubber in the mixer, sheet the rubber 3-5 times, make triangle bags 3-5 times to obtain a film, park it for 12 hours, and then extrude it into a film using a cold feed extruder; D. Put the formed film obtained in step C into a flat vulcanizer for vulcanization treatment; the parameters of the vulcanization treatment are as follows: vulcanization temperature 150-170° C., vulcanization time 10-20 min, pressure 12-18 MPa.

10. Application of a low-temperature, high-elastic, UV-resistant rubber pad according to any one of claims 1 to 8, characterized in that: Rubber pads are used in railway lines.

Citation Information

Patent Citations

  • Preparation method for rubber waterproof coating film

    CN109554031A